Mapping of radial glia and of a new cell type in adult canary brain - Alvarez-Buylla, A (J Neurosci, 1988)
Frontal and coronal sections of adult male and female canary brain were stained with a monoclonal antibody to vimentin using an immunoperoxidase technique; some sections were counterstained with cresyl violet. The position of radial glia cells was mapped using a computer-linked microscope. The telencephalon was found to have a rich set of radial glia. The long processes of these radial glia showed a mediolateral orientation, and were much more abundant in some parts of the telencephalon (e.g., hyperstriatum, caudal neostriatum, and lobus parolfactorius) than in others (e.g., anterior neostriatum, archistriatum, and septum), which had few or no radial glia fibers. A small, elongated cell type not previously described in adult avian brain was frequently seen to be associated with the long processes of the radial glia, oriented in the same direction and often in close apposition. The position of these cells was also systematically mapped, and they were found to be virtually absent outside of the telencephalon. The relation between radial glia fibers and the small, elongated cells was most commonly seen close to the lateral ventricle of the forebrain, where the radial glia cells have their cell bodies. The above observations suggest that there may be a functional relation between radial glia and the small, elongated cells. We hypothesize that the latter cells are young migrating neurons. This hypothesis is tested in a separate publication (A. Alvarez-Buylla and F. Nottebohm, unpublished observations).